EVALUASI KRIM DENGAN VARIASI KONSENTRASI EKSTRAK DAUN MEDANG PIRAWAS (LITSEA ELLIPTICA BLUME): . - Ivan Santoso; Maratu Soleha; Dena Anggraini (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
The content of Litsea elliptica Blume leaves from the results of phytochemical screening is that there are alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, steroids, glycosides, and essential oils. Litsea elliptica Blume has antioxidant activity against radicals with EC50 values of 23.99, 4I.69, 11.2.2, and 33.48 mg/L, respectively, compared to standard butylated hydrokyl toluene. This research is quantitative and descriptive. The population in this study was the Medang Pirawas leaf plant (Litsea elliptica Blume). The thick extract preparation used in this research was obtained using the maceration method. This research aims to find the best formula for making cream preparations through quality and stability tests. The preparation of Litsea elliptica Blume extract cream using various extract concentrations of 0.1%, 0.15%, and 0.2% was carried out for 4 weeks by testing pH levels, viscosity, homogeneity, emulsion type, spreadability, and stability